Art Therapy pada Gangguan Jiwa Halusinasi: Literature Review - Asep Wahyudin Hidayat; Iin Inayah; Dian Kunthi Nugrahaeni; Andria Pragholapati (NHM PRESS, 2022)
This paper reviews the literature on non-pharmacological treatment options for hallucinatory mental disorders and explores art therapy in relation to reducing hallucinatory symptoms. This review attempts to start a discussion and encourage further research in the area of ​​expressive arts regarding the growing need to conceptualize our understanding of the role of art therapy in the treatment of hallucinatory mental disorders. Research highlights Art therapy can reduce hallucinatory symptoms in people with mental disorders (ODGJ).